Patients with retinoblastoma and chromosome 13q deletions have increased chemotherapy‐related toxicities. Issue 11 (13th July 2016) - Brennan, Rachel C.; Qaddoumi, Ibrahim; Billups, Catherine A.; Kaluzny, Tracy; Furman, Wayne L.; Wilson, Matthew W.
Abstract: Background: A total of 5–10% of patients with retinoblastoma (RB) harbor deletion of the long arm (q) chromosome 13 (13q‐). The treatment‐related toxicities in this population have not been described. Methods: Sixty‐eight RB patients on a single institutional protocol (RET5) from 2005 to 2010 were reviewed. Genetic screening identified 11 patients (seven female) with 13q‐. Patients with early (Reese‐Ellsworth [R‐E] group I–III) disease (6/23 with 13q‐) received eight courses of vincristine/carboplatin (VC). Patients with advanced (R‐E group IV‐V) bilateral disease (2/27 with 13q‐) received two courses of vincristine/topotecan (VT) followed by nine courses of alternating VT/VC. Patients undergoing upfront enucleation received histopathology‐based chemotherapy: intermediate risk (2/8 with 13q‐) or high risk (1/10 with 13q‐). Dose reductions were mandated for >7 day delay in two consecutive courses following hematologic toxicity. Grades 3 and 4 hematologic, infectious, and gastrointestinal toxicities were compared between RET5 patients with and without 13q‐. Results: Demographics were similar between groups. When present, prolonged neutropenia (median 7 days, range 0–14 days) delayed chemotherapy and resulted in more frequent dose reductions among 13q‐ patients (5/11) than non‐13q‐ patients (4/57) ( P < 0.01). GI toxicity was similar between groups (5/11 13q‐ vs. 13/57 non‐13q‐; P = 0.14), but halted chemotherapy in one 13q‐ patient. Infectious complications and disease outcomes were similar between groups. At follow‐up, all patients are alive (median 6.1 years, range 7.6 months–9.5 years). Conclusions: 13q‐ RB patients had a higher incidence of neutropenia requiring chemotherapy dose reductions, but did not have increased treatment failure.